2019
DOI: 10.1007/978-3-658-25769-9_5
|View full text |Cite
|
Sign up to set email alerts
|

The Democratic Biopolitics of PrEP

Abstract: for criticism, comments, and remarks which helped enormously to develop the argumentation of this chapter. 2 point for the destigmatization of gay sexuality and transformation of gay subjectivity. 'Biopolitical democratization' entails making explicit how medical technology and health care relates to sexual subjectification and ethics, to strengthen the voice of (potential) PrEP users in health politics, and to renegotiate the profit and power of Big Pharma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
0
9
0
4
Order By: Relevance
“…participation, that is political and ethical deliberation of biopolitical developments, is something to be valued and supported. I have developed such a concept of democratic biopolitics in my discussion of HIV-Pre-Exposition-Prophylaxis (PrEP) and I have shown that PrEP is not (only) a strategy of big pharma to make money, but actively desired by and developed with the gay community (Schubert, 2019). PrEP is part of an ethical re-negotiation of sex in the gay community and can help to destigmatize sex and fight homonormativity.…”
Section: Democratic and Populist Biopoliticsmentioning
confidence: 99%
“…participation, that is political and ethical deliberation of biopolitical developments, is something to be valued and supported. I have developed such a concept of democratic biopolitics in my discussion of HIV-Pre-Exposition-Prophylaxis (PrEP) and I have shown that PrEP is not (only) a strategy of big pharma to make money, but actively desired by and developed with the gay community (Schubert, 2019). PrEP is part of an ethical re-negotiation of sex in the gay community and can help to destigmatize sex and fight homonormativity.…”
Section: Democratic and Populist Biopoliticsmentioning
confidence: 99%
“…Wir verdeutlichen diese Aspekte nun durch zwei Beispiele: Die Subjektivierung in migrantischen Selbstorganisierungen (Schwiertz 2019(Schwiertz , 2021b und in schwulen Subkulturen (Schubert 2019(Schubert , 2020c(Schubert , 2021. 14 Das Beispiel der migrantischen Selbstorganisierungen zeigt, dass aktive Identitätskonstruktionen eine Bedingung emanzipativer Politik sind, gerade um überhaupt eine öffentlich wirksame Sprechposition erlangen zu können.…”
Section: Subjektivierungunclassified
“…Villa 2007). Die poststrukturalistische Theorie, insbesondere Foucaults Genealogie der Erfahrung der "Sexualität", hat für die Entwicklung eines solchen queeren Denkens, das auf die Kritik von Heteronormativität und Zweigeschlechtlichkeit abzielt, sowohl auf feministischer und lesbischer Seite (Maihofer 1995;Meißner 2010) als auch innerhalb der schwulen Theorie (Halperin 1995;Schubert 2019Schubert , 2021, eine zentrale Rolle gespielt. Am früheren Differenzfeminismus wurde entsprechend kritisiert, dass die Kategorie "Frau" zu heterogen ist, um sie ohne Weiteres zur Basis eines politischen Projekts zu machen, insbesonders weil biologische Geschlechtsmerkmale für die Analyse konkreter Diskriminierungsverhältnisse nicht ausreichend seien und erst durch ihre Intersektion mit heteronormativen, kapitalistischen, rassistischen (Federici 2012 Butler (1999Butler ( , 1995c (Butler 1995b, S. 50).…”
unclassified
“…The complex reasons for the extreme epidemic of Black gays or non-gay-identifying MSM and the difficult attempts to bring PrEP to their communities is beyond the scope of this article (Villarosa 2017). 4 Parts of the material of this section and of sections 4 and 5 have been previously published in Schubert (2019).…”
Section: Prep -The Medicalization Of Hiv Preventionmentioning
confidence: 99%